60.8k views
4 votes
Write the expression as a square of a binomial:

0.01x^4+y^2–0.2x^2y

^=square

User Bolov
by
5.3k points

2 Answers

5 votes

That would be

(0.1x^2 - y)^2

Check:-

If we expand this (0.1x^2 - y)(0.1x^2 - y)

it = 0,01x^4 - 0.1x^2y - 0.1x^2y + y^2

= 0.01x^4 + y^2 - 0.2x^2y

User Crtag
by
5.4k points
5 votes


0.01x^4+y^2-0.2x^2y=\\\\= 0.01x^4-0.2x^2y+y^2 =\\\\=\Big(0.1x^2\Big)^2-2\cdot0.1x^2\cdot y+\Big(y\Big)^2=\\\\=\boxed{\bf \Big(0.1x^2-y\Big)^2}



User Natily
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.